Melissopallinology characterization of Portuguese honeys with protected designation of origin - Almeida, Paulo Ruddo (2024)
The European Union created, through Regulations No. 2081/92 and No. 2082/92, Protected Designation of Origin (PDO) as an instrument for valuing agricultural products with distinctive particularities, demanding for this purpose the establishment of requirements set out in a specification book.